BUMDes Untuk Desa: Kinerja BUMDes dalam Meningkatkan Perekonomian di Yogyakarta - Deni Setiawan (Pencerah, 2021)
BUMDes in DIY Yogyakarta has the potential and opportunities to be developed because villages in DIY Yogyakarta need effective guidance and management for the welfare of village communities through the BUMDes. Village Law number 6 of 2004, the government makes a policy whereby villages should be able to establish BUMDes, but Yogyakarta Yogyakarta still has villages that do not yet have BUMDes especially in villages that have the potential to develop business types. This research is descriptive qualitative research that aims to describe the role of BUMDes Amarta, Srimartani Makmur and Panggunglestari in improving the village economy. This can be seen from the type of business being developed. The population in this study were BUMDes members consisting of 3 (three) villages. Data were collected through interviews with BUMDes members and analyzed using Nvivo 12 plus descriptively. BUMDes Amarta, Srimartani, and Panggunglestari have their ideas and characteristics. 3 factors influence the performance of BUMDes, namely individual factors, psychological factors, and organizational factors. The results show that individual factors have a large or dominant role in efforts to improve the village economy.